ประสบการณ์ในการปรึกษาเชิงจิตวิทยาวินิตของนิสิตระดับปริญญาโท สาขาวิชาจิตวิทยาการปรึกษา - กชวร จุ๋ยมณี (จุฬาลงกรณ์มหาวิทยาลัย, 2005)
The purpose of this research was to study experiences in counseling practicum of the counseling master students by using the qualitative research method of a phenomenological inquiry. The research participants were 15 counseling psychology master students from the Faculty of Psychology, Chulalongkorn University, who registered in Practicum in Counseling of the first semester, 2004 academic year. Data were collected through focus group technique, students logs and participants s observation. The findings were categorized into 6 themes of experiences from 2 phases: 1. pre-counseling practice experiences and 2. during and post counseling practice experiences. Two themes of experiences from pre-counseling practice were emerged: 1) Anticipating to gain something from the practicum and 2) Preparation for practicing. Themes from periods of during and post counseling practice experiences were 3) Difficulties and obstacles in counseling practice 4) Increasing of professional capacities in supporting, encouraging and helping atmosphere 5) Professional learning and 6) Extra values from counseling practice.